2009
DOI: 10.1136/bjo.2009.158568
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of corneal biomechanical properties and intraocular pressure with the Ocular Response Analyzer in childhood myopia

Abstract: Lower CH and CRF were associated with longer AL but not corneal curvature. The association between lower CH and deeper ACD demonstrated the importance of CH as a determinant of ocular biometry in both the anterior and posterior segments. Differences in corneal biomechanical properties may indicate more generalised structural differences between eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
43
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 24 publications
14
43
5
1
Order By: Relevance
“…Results in other studies are inconclusive in this regard. Chang et al 26 studied a sample of subjects similar to our students in age; in agreement with our findings, they found no significant change in the CRF or CH with age. Similarly, Lim et al 10 observed no significant change in these indices with age in their sample of 12-to 15-year-olds.…”
Section: Discussionsupporting
confidence: 94%
“…Results in other studies are inconclusive in this regard. Chang et al 26 studied a sample of subjects similar to our students in age; in agreement with our findings, they found no significant change in the CRF or CH with age. Similarly, Lim et al 10 observed no significant change in these indices with age in their sample of 12-to 15-year-olds.…”
Section: Discussionsupporting
confidence: 94%
“…Our new findings included identification of less viscous damping and less whole eye movement of myopic eyes. Several previous studies using the ORA have reported lower CH values in myopic eyes, 9,21,22,24 which agrees with the current study in which less viscous damping capacity was seen in eyes with a longer axial length.…”
Section: Axial Lengthsupporting
confidence: 83%
“…In addition to ocular pathologies, the corneal biomechanical parameters are associated with a range of ocular and systemic factors. The ORA parameters are affected by various baseline factors such as refraction, 8,9 axial length, [21][22][23][24] age, 23 IOP, 23 corneal curvature, 23 and central corneal thickness (CCT). 25 Parameters measured with the Corvis ST are associated with the axial length, 26 age, 27,28 diabetes, 29 IOP, 13,25,[30][31][32] corneal curvature, 26,33 and CCT.…”
mentioning
confidence: 99%
“…This is especially important in light of the need to acquire statistically significant material property data, which is difficult to obtain from human donor corneas. The biomechanical metrics provided by ORA and CVS are all associated with corneal deformation under air pressure, and hence are expected to be influenced by IOP, corneal thickness, material properties of the cornea, and to a lesser extent the sclera, and in addition factors that affect the material properties such as: corneal health and medical conditions (Chang et al, 2010;Kotecha et al, 2006;Luce, 2005;Sullivan-Mee et al, 2008;Tas et al, 2013). These metrics, therefore, if understood properly, have the potential to be used to improve accuracy of measuring IOP, and as indicators of the biomechanical state of the cornea, clinical diagnosis of eye some diseases, such as keratoconus, where corneal stiffness undergoes notable deterioration.…”
Section: Resultsmentioning
confidence: 96%
“…Clinically measured metrics provided by ORA and CVS have been widely used to assess the biomechanical response of the cornea (Leung et al, 2013;Pinero et al, 2010), with all of the metrics relying on the morphologic response of cornea to the action of the instruments' air puff indentation. Current evidence points at effects of IOP and CCT on some of ORA and CVS mechanical metrics (Chang et al, 2010;Kotecha et al, 2006), and while it is expected that the metrics will be related to the cornea's and possibly the sclera's biomechanical behavior, the link between these metrics and the established mechanical properties of tissue (such as tangent modulus and Poison's ratio) has not been established yet.…”
Section: Introductionmentioning
confidence: 98%